DEVELOPMENTAL HISTORY OF CHARACTER EDUCATION AND HOW IT COULD BE DEFINED - Muhammad Ahkam Arifin (Institut Agama Islam Negeri (IAIN) Bone, 2017)
The central theme of this paper discusses the developmental history of character education (CE) and some definitions that have been referred to it. It first explores the historical development of character education that is mostly sourced in American history. Within this section, it is shown that character education seemed to decline between 1940s and 1960s, yet such other approaches to character education started emerging as `values clarification` and `moral dilemma discussion`, although they both appeared to have different underlying theories. It then moves to some definitions of character education that have been put forward by different experts in the field; within the same title, the author of current paper also provides his own definition based on the mentioned facts.